RESEARCHES ON THE INFLUENCE OF SOIL AND CLIMATE CONDITIONS IN THE ROMANIAN PLAIN AND TECHNOLOGICAL CHAINS ON THE CAPACITY TO MAINTAIN THE APPLES QUALITY-CASE STUDY - Nicoleta OLTENACU; Andrei Radu IOVA; Elena LASCAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The success of fruit storage in storehouses is conditioned and depends largely on the environment factors, on applied technology and storage conditions. The better the optimal factors are known on which the growth and formation of the fruit depends, when and how to manipulate and transport the fruit, the more secure the premise for the success for the good preservation of fruit is. It is absolutely necessary to know the main factors that must be taken into account in order to bring into storehouse only fruit corresponding to this purpose. The experiments were organized in comparative variants in the case of apples based on 6 homologated varieties of apple (Florina, Generos, Golden Delicious, Idared, Jonathan and Redix) present in the current assortment in Moara Domneasca farm and in Romania. After 120 days of storage, determinations were made concerning: evolution of the soluble dry matter content; evolution of some components; organoleptic appraisal (appearance, firmness, taste). The results showed that, after storage, the dry matter content, the titratable acidity, the total sugar content and the vitamin C content recorded an increased or decreased evolution depending on variety, compared to the initial content.